A review on the determination heavy metals ions using calixarene-based electrochemical sensors - Chong, Jin Mei; Alang Ahmad, Shahrul Ainliah (Elsevier, 2021)
In aquatic environment, the presence of heavy metal in excess than permissible limits set by the World Health Organization (WHO) can cause problems to human being and aquatic life. Hence, various analytical methods have been developed to monitor the water quality by tracing different heavy metal ions in water samples. The present review summarizes the body of work (143 studies) on heavy metal determination in the past 20 years using electrochemical sensors and calixarene derivatives. The potential of calixarene derivatives to sense heavy metal ions using different electrochemical techniques were discussed. The review begins with the introduction of various electrochemical methods including potentiometry, amperometry, voltammetry and electrochemical impedance spectroscopy along with the general setup. This review provides an overview of the mechanism, main parameters of studies and application of calixarene derivatives in selective and sensitive detection. The detection of various target analytes, concentration range, and detection limit using calixarene derivative-based sensors, with different electrochemical techniques, are presented. The strengths and weaknesses of different electrochemical techniques based on calixarene derivatives are also discussed. The review shows that calixarene derivatives have great potential in sensing technology applications, specifically in heavy metal ion determination. In the end, present challenges and future prospects for translating developed sensors into portable sensing in commercial purposes is highlighted.